Effect of column aspect ratio on punching strenght of concrete flat-plates - Özden, Özlem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2001., 2001)
Traffic congestion is a serious problem seen in crowded areas like Istanbul. It does not only cause considerable time losses, but also causes waste of resources because of increase in fuel consumption and monetary cost of waiting time. Furthermore, it causes air and noise pollution. Signal optimization has a very important role in organizing the traffic flow. By optimizing the signal timings, time losses can be prevented, fuel consumption can be reduced and environmental harms can be minimized. There are various softwares used for signal optimization. In this study, Signal97 package has been used in the analyses of the intersections and for optimization of signal timings. To check the validity of the package, a comparison study was performed using the field values and Signal97 estimations. It was found that there is a statistically good relation between the field values and Signal97 estimations proving the validity of the software for further uses.The signal optimization study made for Sarayburnu, Ahırkapı and Silivrikapı intersections in Istanbul showed that, a considerable amount of benefit was obtained for these intersections by reducing the delays and fuel consumption. The monetary equivalent of this benefit was calculated to be approximately 71.000.000.000 TL (104.000,00 USD) per year. Considering that this value is only for three intersections, the importance of signal optimization becomes quite clear.
Keywords: Plates (Engineering)